Variable carbon and chlorine isotope fractionation in TCE co-metabolic oxidation. (March 2020) - Gafni, Almog; Gelman, Faina; Ronen, Zeev; Bernstein, Anat
Abstract: Identifying co-metabolic TCE oxidation in polluted groundwater is challenging due to lack of indicative by-products. This challenge may theoretically be resolved if the oxidation process can be characterized by a distinct dual isotope enrichment. In this work, we aimed to explore the carbon and chlorine isotope effects associated with TCE oxidation by a variety of oxygenases. These included pure strains and enrichment cultures of methane, toluene and ammonia oxidizers, as well as experiments with crude extracts. Isotope effects determined for TCE oxidation by toluene and ammonia oxidizers were mostly in line with expected values for epoxidation mechanism (ϵ 13 C −11.0 ± 0.7 to −24.8 ± 0.2‰ and ϵ 37 Cl +0.9 ± 0.5 to +1.0 ± 0.4‰), whereas, the methanotrophs resulted in distinctively different isotope effects (ϵ 13 C −2.4 ± 0.4 to −3.4 ± 0.8‰ and ϵ 37 Cl −1.8 ± 0.2 to −2.9 ± 0.9‰). It is suggested that in TCE oxidation by methanotrophs, substrate binding rather than bond cleavage is rate limiting, leading to this unexpected isotope effect. On the environmental level, our results imply that the oxidative process can be differentiated if catalyzed by toluene and ammonia oxidizers or by methanotrophs. Additionally, the oxidative process can be distinguished from the reductive one. However, using dual isotope analysis in the field may result in an under-estimation of the overall co-metabolic process if methanotrophs are to be excluded due to low isotope effects. Graphical abstract: Image 1 Highlights: Dual isotope fractionation in co-metabolic TCE oxidation was studied. Different isotopic effects for methanotrophs vs. toluene and ammonia oxidizers. Substrate binding is suggested as degradation rate limiting in TCE oxidation by methanotrophs. Applicability of dual isotope analysis in polluted groundwater is challenging.